PENGELOLAAN PERIKANAN BERBASIS HUKUM ADAT MELALUI MODEL CO-MANAGEMENT - Josef M Monteiro (Arena Hukum, 2021)
AbstractThis research examines the Lamaholot customary law as an idea or unwritten customary idea but contain ethics and morals, in the form of a belief system, rituals, abstinence, and sanctions, which are then accommodated into a co-model management. This research becomes important to assist the top law enforcement fisheries management violations committed by traditional fishermen in the district East Flores and Lembata Regency, East Nusa Tenggara Province. This empirical legal research uses a statutory approach, the concept of legal anthropology with a socio-legal perspective, and cases. The results shows the number of cases of violations of fisheries management by traditional fishermen still high in the last few years. This proves that law enforcement has not been effective both from the structure, legal substance and culture. To overcome this, it is necessary to re-institutionalize customary law through a co-management model, namely the local government and law enforcement agencies forming a partnership model with customary stakeholders or functionaries to function re-belief systems, rituals, customary sanctions and mechanisms in the enforcement process law against traditional fishermen who exploit fishery resources illegally.Â AbstrakPenelitian ini mengkaji hukum adat Lamaholot sebagai ide atau gagasan adat yang tidak tertulis tetapi mengandung etika dan moral berupa sistem kepercayaan, ritual, pantangan, dan sanksi, yang selanjutnya diakomodir ke dalam sebuah model co-management. Penelitian ini penting dilakukan untuk membantu penegakan hukum atas pelanggaran pengelolaan perikanan yang dilakukan oleh nelayan tradisional di Kabupaten Flores Timur dan Kabupaten Lembata, Provinsi Nusa Tenggara Timur. Penelitian hukum empiris ini menggunakan pendekatan peraturan perundang-undangan, konsep antropologi hukum dengan perspektif sosio-legal, dan kasus. Hasil penelitian menunjukkan beberapa tahun terakhir jumlah kasus pelanggaran pengelolaan perikanan oleh nelayan tradisional masih tinggi. Hal ini membuktikan penegakan hukumnya belum efektif baik dari struktur, substansi dan budaya hukum. Untuk mengatasinya perlu pelembagaan kembali hukum adat melalui model co-management dimana pemerintah daerah dan lembaga penegak hukum membentuk model kemitraan dengan pemangku atau fungsionaris adat untuk memfungsikan kembali sistem kepercayaan, ritual, sanksi adat dan mekanisme dalam proses penegakan hukum terhadap nelayan tradisional yang memanfaatkan sumber daya perikanan secara ilegal